VOF/FVM prediction and experimental validation for shear-thinning fluid column collapse. (January 2015) - Moraga, Nelson O.; Lemus, Luis A.; Saavedra, Mario A.; Lemus-Mondaca, Roberto A.
Abstract Dam break problems for non-Newtonian fluids can be found in sudden collapse of mine tailings, snow avalanches, debris and lava flows, and casting solidification. A numerical simulation and experimental validation of collapse of a shear-thinning fluid column with a high viscosity is presented. The 2D fluid mechanics, described in terms of the non-linear coupled continuity and momentum equations, was solved by the finite volume method (FVM) with the Pressure Implicit with Splitting of Operators (PISO) coupling algorithm and the volume of fluid method (VOF). The shear-thinning fluid column that collapses was described by the rheological model of Carreau–Yasuda. The numerical results obtained for the instantaneous position of the free surface were validated with 7% accuracy in comparison with experimental measurements, determining that when a small container is used the walls affect the transport of fluid, causing a creeping flow.